Impact and thermal properties of tin slag polyester composite / Ahmad Ramli Rashidi ... [et al.] - Rashid, Ahmad Ramli; Zolmahadi, Nurul Shafika; Md Zaidi, Nurhanis Farisha; Jihat, Danish Akmal
The properties of the tin slag/ polyester have been assessed experimentally by using DSC (Differential Scanning Calorimetry) and impact method. The amount of the Tin slag mixed with the Polyester is varies. MEKP was added to the mixture as a hardener with a small amount to ensure the tin slag and the polyester is mix. The amount of the MEKP added to the tin slag/polyester mixture is 1%. The mixture is tested by using Impact Strength Test and DSC. The DSC experiment reveals the thermal properties of the tin slag/polyester. The results of the experiment are different from the sample ratios. The reason of this is due to the amount of tin slag being introduced to the polyester. Another reason is that the dispersion of the tin slag in the tin slag/polyester mixture when preparing the sample. The Impact experiment shows that different ratios of the tin slag/polyester mixture indicates different impact resistance. The impact resistance indicates the amount of the energy can be absorbed by the sample when the impact experiment was conducted. The experiment of Impact resistance was conducted with all the ratios of the mixture of the tin slag and the polyester including pure polyester to sec the difference of the impact resistance of each of the tin slag/ polyester mixture.